THE DELAY AND FALL IN MARRIAGE IN US: AN ANALYSIS OF HOW THE ECONOMIC GROWTH IMPACTS THE DECISION TO MARRY AND A LOOK FORWARD TO THE FUTURE - Salman Hussain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In the last century after WW2 we have seen advances in the overall economic development of the world and a tremendous rise in education and health. Women across the countries felt the wave of feminism and rise in their welfare through more awareness, education and the better healthcare facilities. With these trends one particular trend can be seen: the fall in the marriage rate in the population and delay of the marriage. This phenomenon can be seen in the good lights that increase in the median age of marriage means less child marriage and people marrying at a mature age. But like everything else, it also carries some future problems. This study is aimed at the finding the potential relationships of this phenomenon with the probable causes behind it like economic growth, expansion in healthcare or expansion in education levels in both man and woman and analysing some potential problems that may arise along with it in the United states of America.